Parents' labour force participation and children's involvement in work activities: evidence from Thailand. (2nd July 2020) - Yokying, Phanwin; Floro, Maria S.
ABSTRACT: This study provides a better understanding of children's engagement in economic work and housework by examining its relationship with parents' labour force participation. It also explores how parents' employment type is associated with children's involvement in work activities. Using Thailand's Labour Force and Time Use Surveys, our multivariate probit regression results show that girls actively participate in economic activities when their mothers are employed, while boys' involvement in such work is positively correlated to both parents' employment. Girls' housework participation is also positively associated with parents' employment, suggesting that their assistance in household chores enable their parents to stay in the labour market. These positive relationships are prevalent particularly among children with either mothers or fathers working informally. Hence, the findings suggest that anti-poverty or expansionary policies aimed at increasing labour force participation without attention to job quality, social protection and care needs can adversely affect children by increasing their need to work.